CUBE ON ZAMKOVAYA HORA IN KYIV AS A UNIQUE EXOGENOUS OBJECT OF ART - Konovalova, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
This article analyzes special aspects of the social existence of Station-1 objet d’art, a 108 cm brick cube, on Zamkovaya Hora hill in Kyiv. Created in 2001, this art object is an accumulating visiting center for different social strata, from representatives of informal youth associations to tourists and experts in local history. Transformations of the cube surface are viewed as a range of endless ‘modular combinations’ (Didi-Huberman). Watching people contact with an art object beyond art institutions proves the endlessness of manifestations of both vandalism (destruction) and creativity (poems and texts on the cube planes).